The age of partners and the duration of the relationship versus the quality of close emotional relationships - Jarecka, Karolina (Kwartalnik Naukowy Fides et Ratio, 2022)
The quality of emotional relationships depends on the individual characteristics of the partners but, above all, on the relational factors responsible for integrating or risking disintegrating the relationship. Their assessment requires taking a time perspective into account. Each lasting relationship experiences changes in its quality, which may be related to the age of the partners and the time of their life together. The aim of the research was to assess the connection between the age of partners and the length of their relationship and the quality of close relationships, including mutual communication, intimacy and conflict behaviour. They are recognised as key to the quality of the relationship, but it is still open to question how they change over time. The study involved 696 people aged 20-68, including 360 women and 336 men. The respondents were classified into three groups significant for human development, including 16-year age ranges. In the first group, there were 240 people aged 20-35 years (i.e., in early adulthood), the second group consisted of 276 people aged 36-51 years (which is considered appropriate for middle adulthood), and the third group of 180 people aged 52-68 (i.e., in the period associated with the second half of middle age and entering late adulthood). The respondents were in a lasting relationship from one year to 47 years. The research used a socio-demographic survey questionnaire and K. Halweg’s Partner Relations Questionnaire in the Polish adaptation of I. Janicka. It was found that with the age of the partners and duration of the relationship, the number of conflict behaviours increase and the intimacy and mutual communication important for its integration weakens. The most vulnerable to these types of changes are spouses in the second half of middle adulthood and entering old age. Potential processes driving these findings are discussed. The age of the partners and the related seniority of the relationship may lead to changes in its quality. However, they cannot be regarded as sufficient to assess changes in close relationships.